The Effects of Combination Herbal Medicine Tablet on Migraine Headache: A Randomized, Double-blind, Placebo, Controlled Study - Sarah Mousavi; Mohammadreza Zare Bidaki; Naghmeh Yazdi; Vahid Tafazoli; Masoud Sadeghi Dinani (Research Center for Rational Use of Drugs (RCRUD), 2024)
Background: Migraine is the second most common cause of headache, various methods have been mentioned for the treatment of migraine, including herbal medicine. Iaraj Fiqra is a combination of Aloe, saffron, cinnamon, mustalci, balsam incense and asaroon and claim to be effective in migraine. The present study aims to compare the effect of Iaraj Fiqra and placebo tablets on migraine headache. Methods: In this randomized, controlled trial, patients with migraine (based on the International Headache Society definition) received Iaraj Fiqra (500mg/daily) or placebo tablets for two months. Headache characteristics were measured using the Migraine Disability Assessment (MIDAS) and Headache Impact Test-6 (HIT-6). Results: Iaraj Fiqra reduced significantly the frequency (P=0.007), the severity (P=0.000) and the duration (P=0.000) of attacks compared to placebo. MIDAS and HIT-6 scores were significantly reduced in the drug group other than the placebo group (P=0.014 and P=0.000 respectively). Analgesic use also reduced. No significant difference was observed between the two groups in term of side effects (P=0.23). Conclusion: This study showed that Iaraj Fiqra had significant effects on reducing headache characteristics and analgesic use and given its limited side effects, it is recommended for the treatment of migraine. J Pharm Care 2024; 12(1): ?.